Expressão de três genes relacionados à virulência em estirpes leptospirais do sorogrupo Sejroe após subculturas semanais - Correia, L.; Malliagros, L. V.; Brasil, T.; Pires, B. C.; Jaeger, L. H.; Carvalho-Costa, F. A.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Bovine leptospirosis is characterized mainly by reproductive problems associated with infections by strains of serogroup Sejroe. Pathogenic strains belonging to same serogroup could present differences in pathogenicity, suggesting existence of unknown molecular mechanisms involved in virulence. Furthermore, it is known that subculture of strains can lead to attenuation of virulence by changes in protein coding genes.